KAJIAN FORMULASI ( BAHAN BAKU , BAHAN PEMANTAP ) DAN METODE PEMBUATAN TERHADAP KUALITAS ES KRIM - Endang Sri Hartatie (Jurnal Gamma, 2011)
Endang Sri HartatieStaf Pengajar Jurusan Teknologi Industri Peternakan, Fakultas Pertanian Peternakan.Universitas Muhammadiyah MalangAlamat Korespondensi : Jl. Danau Diatas F 1B4 MalangTelpon : 0341 713191, Hp : 085646419060ABSTRACTThe purpose of this research was to get ice cream formula with sensory characteristic thatpreferred by consumer and to know ice cream quality that processed with convensional methodeand machine methode.The experimental design used was Ramdomized Complete design with two factors and threerepetition. The first factor was ice cream formula and the second factor was the processing methode( convensional and machine methode)The result of this research showed that the ice cream formula, processing methode and interactionbetween treatments had significant effect ( P < 0,05 ) on overrun. Prefer of panelis on ice creamproduct was depend on sensory characterisric of ice cream and sensory characteristic of ice creamwas depend on raw material quality. Ice cream composition ( fat, solid non fat, water content, sugarand stabilizer) and processing methode. Proceesing methode ice cream with machine was betterquality ice cream thsn convensional methode.